False promises : the shaping of American working class consciousness - Aronowitz, Stanley (e-Duke books scholarly collection., 1992)
This classic study of the American working class, originally published in 1973, is now back in print with a new introduction and epilogue by the author. An innovative blend of first-person experience and original scholarship, Aronowitz traces the historical development of the American working class from post-Civil War times and shows why radical movements have failed to overcome the forces that tend to divde groups of workers from one another. The rise of labor unions is analyzed, as well as their decline as a force for social change. Aronowitz's new introduction situates the book in the.